Local Wisdom of Malayu Ethnics to Strengthen Pontianak Youth Identity West Kalimantan - Rustam Rustam (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
This study aimed to produce Guidance and Counseling media with Malay ethnic local wisdom, which focused on reinforcing the identity of Pontianak youth. The phenomenon of adolescents in Pontianak does not recognize the inheritance of local wisdom values that influenced behavior and lifestyle. The paradigm in this research was social constructivism, focusing on the nature of change that took place continuously and structured. The method in this study used a compiled Hermeneutic type qualitative approach, examines the text and context of the local wisdom of the Malay ethnic, namely Saprahan. This aimed to find the potential elements forming the identity of Pontianak youth. The validity system used was by Triangulation, Intersubjectivity Validation, and peer review. It was needed a media of Bibliocounseling with local wisdom that could illustrate the patterns of thought and the process of cultural internalization related to the control of the lifestyle of adolescents. Potential elements of local wisdom, Saprahan forming teen identity which containing in the Bibliocounseling media included religious identity, civilized, gathering (silaturahmi), unifying, harmonious in ethnicity, soul narrator, hard worker, sharing, firmness or strong soul, cooperation, friendship, authenticity, friendliness, and polite.